Processos de identificação e políticas da (in)diferença - Röhrig, Adriana; Cantarelli, Ana Paula; Ourique, João Luis Pereira; Umbach, Rosani Úrsula Ketzer (Literatura e Autoritarismo, 2011)
Apresentação